2007
DOI: 10.1007/s10529-007-9349-y
|View full text |Cite
|
Sign up to set email alerts
|

Secretory fluorescent protein, a secretion green fluorescent fusion protein with alkaline phosphatase activity as a sensitive and traceable reporter in baculovirus expression system

Abstract: The advantages of using traceable fluorescent protein (enhanced green fluorescent protein; EGFP) and a secretory alkaline phosphatase (SEAP) have been used to generate a reporter gene: the secretory fluorescent protein (SEFP). Sf21 cells, infected with the recombinant baculovirus containing the SEFP gene, revealed both traceable fluorescence and easily detectable alkaline phosphatase activity in the culture medium. The distribution of SEFP within the cells revealed that it was excluded from the nucleus, implyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is expected that the amount of biomarker entering blood may change with respect to tumor size, angiogenesis and necrosis. Interestingly, this fraction may now be better studied in small animal models in vivo using intravital microscopy (44) to monitor the intratumoral distribution of fluorescent secretable biomarkers such as SEGF (45) in tumor-bearing animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that the amount of biomarker entering blood may change with respect to tumor size, angiogenesis and necrosis. Interestingly, this fraction may now be better studied in small animal models in vivo using intravital microscopy (44) to monitor the intratumoral distribution of fluorescent secretable biomarkers such as SEGF (45) in tumor-bearing animals.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that the amount of biomarker entering blood may change with respect to tumor size, angi- ogenesis, and necrosis. This fraction may now be better studied in small-animal models in vivo using intravital microscopy (43) to monitor the intratumoral distribution of fluorescent secretable biomarkers such as secretory fluorescent protein (SEFP) (44) in tumor-bearing animals. New biomarkers are constantly being discovered, and each will need to be systematically and rigorously evaluated for its potential to distinguish between healthy and early cancer states.…”
Section: Discussionmentioning
confidence: 99%
“…The pCMV-DRhirSE plasmid contains a SEAP reporter gene fused in-frame with an egfp fluorescent gene. Thus the activity of the RhPV IRES can easily and sensitively be monitored from the medium by the SEAP activity [24] . Six different cell lines were transiently transfected with the pCMV-DRhirSE plasmid, and all transfected cells could be identified by the cap-dependent translation of the DsRed gene under a fluorescent microscope (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Co-expression of two proteins, one a molecular marker and the other the target gene, is a valuable tool for monitoring protein translation. [28][29][30] Several studies have demonstrated that the enhanced green fluorescent protein can be used efficiently as a reporter protein for fast selection of recombinant baculoviruses and viral titer measurements, 31,32) as depicted in Fig. 1B and C. Screening with insect cell lines for rhIFN-expression was carried out in a serumsupplemented medium (Fig.…”
Section: Expression and Purification Of Recombinant Human Interferon-mentioning
confidence: 99%